A dynamic image of the final authority act of local public administrations exercised by issuing building permits. Case study: the South-East Development Region of Romania - Stan, Mari-Isabella (Technium Social Sciences Journal, 2021)
In Romania, territorial/spatial development is understood as the process of transforming the geography of inhabited territories, taking into consideration: territorial planning, urban planning and development, public works, habitat and housing, construction. It is governed by the regulatory framework in force, aligning its policies and strategies with the main reference documents at the European level. The construction sector is a key sector for investment and economic development, playing an important role in achieving the sustainable development objectives through the impact that the quality of construction has on the quality of life and by ensuring the necessary environment for most human activities. The building permit is the final authority act of the local public administration on the basis of which the execution of construction works is allowed in accordance with the measures provided by law regarding the placement, design, construction, operation and post-use of buildings. Starting from comparative structural analyses on the number of building permits issued by the local public administrations in the South-East Region, the objective of this research has been to obtain a dynamic image, through a quantitative assessment, of the number of building permits issued for residential buildings, highlighting the way in which they directly influence the sustainable development of urban and rural localities in the South-East Region of Romania.